The dual pillars of progress: Institutional and cultural dynamics in economic development - Kyriaki I. Kafka (Economies, 2024)
This study examines the critical interplay between institutional and cultural backgrounds and their collective impact on economic development, suggesting that their synchronized evolution-timing, pace, and direction-boosts economic development, while misalignment hinders it. It seeks to determine if these backgrounds complement or substitute each other in fostering economic development. The analysis employs an unbalanced panel dataset encompassing 113 countries across four decades (1980-2019) through a fixed-effects model enhanced by robustness checks (adding control variables, using alternative analysis methods, and applying adjustment criteria). The analysis uncovers a synergistic relationship between institutional and cultural backgrounds in which each element reinforces the other's impact on economic development. Countries with robust institutional and cultural backgrounds exhibit the highest levels of economic development, whereas those with weaker backgrounds experience diminished economic progress. This study further reveals that the influence of institutional background on economic development is more pronounced than that of cultural background. However, this effect is significantly amplified when both institutional and cultural backgrounds are considered. Considering these insights, this study recommends that effective development strategies prioritize simultaneously nurturing institutional and cultural backgrounds. This approach is essential for crafting a successful and comprehensive development roadmap.
Keywords: 330; coevolution; culture; economic development; institutions